Distinct Characteristics of Inferonasal Fundus Autofluorescence Patterns in Stargardt Disease and Retinitis Pigmentosa - Duncker, Tobias (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. To report distinct characteristics of fundus autofluorescence (AF) patterns inferior to the optic disc in recessive Stargardt disease (STGD1) and retinitis pigmentosa (RP). METHODS. Short-wavelength (SW) and near-infrared (NIR) AF images were acquired from patients with STGD1 and RP. In SW- and NIR-AF images of STGD1 patients, gray levels (GL) on both sides of the demarcation line were measured. RESULTS. In STGD1, a demarcation line, which has been assigned to the closed optic fissure, was visible on SW-AF and NIR-AF inferior to the optic disc. In healthy subjects, this demarcation line is only visible by SW-AF. At 20° inferior to the disc center, AF levels on the nasal side were 25% (±11%) lower than on the temporal side in SW-AF images and 18% (±11%) lower in NIR-AF images. For both STGD1 and RP, the inferonasal quadrant exhibited distinct SW- and NIR-AF patterns compared with other fundus areas. Disease-related AF changes, such as flecks, appeared to respect the demarcation line as a boundary. CONCLUSIONS. Disease-related AF patterns originating in RPE in STGD1 and RP appear to respect the demarcation line in the inferonasal quadrant of the fundus as a border. The visibility of the inferonasal demarcation line by NIR-AF in STGD1 but not in healthy eyes may indicate that increased levels of RPE lipofuscin modulate the melanin-related NIR-AF signal. This feature of NIR-AF images may aid in the diagnosis of STGD1 patients.